Main Challenges of Post-Earthquake Renovation in the Case of Zagreb City Center - Anđelina Svirčić Gotovac; Mirjana Adamović; Jelena Zlatar Gamberožić (Journal of Regional and City Planning, 2022)
This paper presents the results of a research on the problems and challenges of post-earthquake renovation in the inner city center of Zagreb, where mostly older, historical buildings are situated, which were severely damaged in the 2020 earthquake. Almost two years after the earthquake, political actors have not been able to make much progress regarding the post-earthquake renovation, which has caused discontent among vulnerable citizens. This paper presents the results of a qualitative analysis of semi-structured interviews with owners of damaged apartments and co-owners’ representatives. The authors found two main issues with the post-earthquake renovation in Zagreb: 1) incomplete renovation and problems with the financing of repairs to damaged buildings, and 2) people moving out of the city center and city apartmanization. The results showed that the cost of damage repair in most cases was covered by the citizens themselves and that institutional help has been slow and bureaucratized. Also, the participation process regarding renovation has not been successful for the citizens and they are still dealing with similar problems as in the beginning of the renovation.